Triphenylamine flanked boron difluoride formazanate for NIR-II fluorescence imaging-guided photothermal therapy. (September 2022) - Li, Hui; Dai, Hanming; Mei, Anqing; Ruan, Xiaohong; Wang, Weili; Yang, Dongliang; Wang, Wenjun; Zhang, Qi; Dong, Xiaochen; Shao, Jinjun
Abstract: Small molecular theranostic agents play the pivot roles in the biomedical field and hold high clinical translational potential. However, it is still difficult to prepare these theranostic agents through a convenient and straightforward synthetic route. Herein, based on the electron-deficient building block boron difluoride formazanate (BDF), we designed and synthesized a novel NIR-II small molecular fluorescent dye (BDF-Ph) by flanking electron-rich triphenylamine units onto BDF to hamper the intermolecular π-π interaction, thus to achieve high fluorescence quantum yield. Then donor-acceptor-donor (D-A-D) structured BDF-Ph was encapsulated into amphiphilic polystyrene- g -poly (ethylene glycol) (PS- g -PEG) to prepare NIR-II fluorescent BDF-Ph NPs. BDF-Ph NPs possessed an emission peak at 975 nm with a high fluorescence quantum efficiency of 0.32% (IR1061, Φ  = 1.7%) and a high photothermal conversion efficiency of 40.1%, making it an excellent NIR-II fluorescent probe for nanotheranostics. In vivo investigation illustrated that BDF-Ph NPs exhibited strong NIR-II fluorescence signals. Meanwhile, upon exposure to 808 nm laser, BDF-Ph NPs could eradicate tumors without apparent adverse effects under the direction of NIR-II fluorescence imaging. These fascinating results confirmed that BDF-Ph NPs as an alternative theranostic nanoplatform could be used for oncotherapy. Highlights: Rational design of D-A-D structured NIR-II small molecular fluorescent dye BDF-Ph. BDF-Ph NPs were prepared by taking amphiphilic PS-g-PEG as the polymer matrix. BDF-Ph NPs showed a high fluorescence quantum efficiency of 0.32% (IR1061, Φ = 1.7%). BDF-Ph NPs showed a high photothermal conversion efficiency of 40.1%. BDF-Ph NPs could eradicate tumors under the direction of NIR-II fluorescence imaging.